IMPLEMENTATION OF SCHOOL LITERACY MOVEMENT IN INSTILLING CHARACTERS TO READ LOW GRADE STUDENT IN THE INTEGRATED ISLAMIC SD LUKMAN AL HAKIM SLEMAN - Yuli Setiawati (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2019)
The purpose of this study is to describe the implementation of school literacy movement in instilling characters to read low-grade students in the integrated Islamic SD Lukman Al Hakim Sleman. This research is included in qualitative research. The design of this research uses a single case study approach for collection through observation, interviews, and documentation. The data analysis techniques in this research use data reduction, data presentation, and conclusions. The validity test in the study uses data source triangulation and triangulation method. The findings of the research is the implementation of school literacy movement in instilling characters to read low-grade students in integrated Islamic SD Lukman Al Hakim Sleman has been implemented using the method of 15 minutes reading. GLS conducted at the integrated Islamic SD Lukman Al Hakim Sleman focuses on reading with the aim of instilling characters to read in low-grade students. Through the implementation of school literacy movement in instilling the optimal character of reading, and motivating and giving the spirit for the students to read will create the character to read the good students and shape the love of Students to Reading.